Multi‐modal Analysis and Modeling of Human Neurodegenerative Disease to Reveal Disease Mechanisms and Biomarkers. (20th December 2022) - Marsh, Samuel E; Murphy, Sarah; Kamath, Tushar; Gazestani, Vahid; Therrien, Martine; Dolan, Michael John; Jereb, Sasa; Reyes, Miguel; Gobom, Johan; Clish, Clary; Hacohen, Nir; Zetterberg, Henrik; et al.
Abstract: Background: Microglia have emerged as key players in the pathogenesis of neurodegenerative conditions such as Alzheimer's disease (AD), taking on distinct transcriptional and functional states. While the ability to profile complex tissues at single‐cell resolution in postmortem brain tissue provides insight into disease‐associated cellular states within the brain, more is required to understand how these changes modulate disease pathogenesis. Building on foundational transcriptomics, the advances in multi‐modal profiling of genomics and proteomics allows for a greater understanding of neuroimmune dysfunction in neurodegenerative disease. Method: Transcriptomic datasets are often confounded by variability in collection and sequencing methodologies. We have optimized tissue dissociation and cell isolation protocols to avoid many of the pitfalls commonly found in bulk and single‐cell transcriptomic studies. Using these optimized protocols, we have begun assessing paired samples (blood, brain biopsy, and cerebrospinal fluid (CSF), from patients at risk for AD to understand neuroimmune changes in early‐phases of AD. We have also characterized the transcriptional and functional responses of human induced pluripotent stem cell (iPSC) microglia in response to a variety of neurodegenerative brain‐relevant challenges, including amyloid, apoptotic neurons and synaptic debris. Result: Using scRNA‐seq on fresh mouse and human tissue we have identified a dissociation‐induced signature in microglia that is highly prevalent in current literature, and developed an experimental methodology to prevent this artifact. We have also identified a similar signature in post‐mortem tissue via snRNA‐seq that may be the result of acute‐pre/post‐mortem processes (Marsh et al., 2022). Powerfully, we also have cerebrospinal fluid (CSF) from the same patients, allowing us to correlate proteomic and transcriptomic analyses to determine the connections between disease‐associated transcriptomic cell states and analyte biomarkers. We can then use the iPSC microglia (iMGLs) to understand how altered transcriptomic states and biomarker profiles may alter microglial functions to elucidate mechanisms by which microglia contribute to disease pathogenesis. Conclusion: Optimization of experimental and analysis methods along with extensive multi‐modal profiling of the same patients will lead to greater understanding of the neuroimmune landscape of neurodegenerative disease to better enable development of novel predictive biomarkers and therapeutic targets.